Direct medical costs of RSV-related bronchiolitis hospitalizations in a middle-income tropical country (2020)
Introduction and objectives With the objective of making informed decisions on resource allocation, there is a critical need for studies that provide accurate information on hospital costs for treating respiratory syncytial virus (RSV)-related bronchiolitis, mainly in middle-income countries (MICs). The aim of the present study was to evaluate the direct medical costs associated with bronchiolitis hospitalizations caused by infection with RSV in Bogota, Colombia. Material and methods We reviewed the available electronic medical records (EMRs) for all infants younger than two years of age who were admitted to the Fundacion Hospital de La Misericordia with a discharge principal diagnosis of RSV-related bronchiolitis over a 24-month period from January 2016 to December 2017. Direct medical costs of RSV-related bronchiolitis were retrospectively collected by dividing the infants into three groups: those requiring admission to the pediatric ward (PW) only, those requiring admission to the pediatric intermediate care unit (PIMC), and those requiring to the pediatric intensive care unit (PICU). Results A total of 89 patients with a median (IQR) age of 7.1 (3.1–12.2) months were analyzed of whom 20 (56.2%) were males. Overall, the median (IQR) cost of infants treated in the PW, in the PIMC, and in the PICU was US$518.0 (217.0–768.9) vs. 1305.2 (1051.4–1492.2) vs. 2749.7 (1372.7–4159.9), respectively, with this difference being statistically significant (p < 0.001). Conclusions The present study helps to further our understanding of the economic burden of RSV-related bronchiolitis hospitalizations among infants of under two years of age in a middle-income tropical country.